EKONOMI POLITIK INSTITUSI ZAKAT: SATU PENELITIAN TERHADAP INSTITUSI ZAKAT DI PULAU PINANG - Najwa, Mohammad (JURNAL SYARIKAH : JURNAL EKONOMI ISLAM, 2017)
Institutional charity is a charity trustee body appointed by the Islamic government for a state or country aimed at governing the collection and distribution of zakat and all related recipients. In Malaysia, zakat management is under the responsibility of His Royal Highness (HRH) Sultan or King. However, for those states that do not have the monarch as Melaka, Sabah, Sarawak and Penang, zakat management is under the responsibility of His Majesty the Yang Di-Pertuan Agong (SPBA). In most states, the management and administration of charity performed by the State Islamic Religious Council (MAIN) and the state government as a representative of each of the sultan or king. Even so, the state of Malacca, Kuala Lumpur, Pahang, Negeri Sembilan, Selangor and Penang, management and administration is carried out by the institutions corporate charity. Out of the total of the country, the management and administration of the zakat institution in Penang is unique because the Penang State Government administration headed by a non-Muslim. The question is, how is the political economy of charity institutions in Penang under the administration of the state government led by the non-Muslim? Are the Penang state government plays a role in determining the direction of zakat institutions governance in Penang? Based on these issues, the study was conducted to identify and analyze the political economy of charity institutions in Penang. This study was performed using two methods of data collection, namely the first, methods study the document; and second, the interview method. The data collected is then analyzed using content analysis. The results of the analysis, it can be concluded three things. First, the establishment of Zakat Pulau Pinang (ZPP) is a strategy Majlis Agama Islam Negeri Pulau Pinang (MAINPP) to strengthen the political economy of charity institutions in Penang. Second, the economy and politics mutually need each other in charity governance institutions in Penang. Third, the political economy of charity institutions in Penang has made zakat governance in Penang more systematic and professional and have a positive impact on the improvement of collection and distribution of zakat in Penang.Keywords: Political Economy, Political Economy Institutions Zakat, Zakat Institution in Penang